Early morning erectile pain in post burn penile contracture - When is appropriate surgical correction indicated? A case report - Chimaobi M. Isiguzo; Ifeanyi I. Onah; Gabriel M. Okorie (Elsevier, 2017)
Penile contracture is an example of intrinsic perineal contracture that can result from poorly managed scalding injury. This resulted in early morning painful erectile pain in a pubertal male. Contracture release corrected deformity and relieved pain. Pre-pubertal surgical correction of penile contracture is indicated to avoid painful erection at puberty. Appropriate referral to specialized centers will improve outcome. Keywords: Erectile pain, Contracture, Penile